Pengembangan Media Replika Tulangan Sloof dan Kolom pada Mata Kuliah Praktek Dasar Batu dan Beton Berbasis Standar Nasional Indonesia (SNI 2847:2019) - Dary Ramadhan Alizar; Laras Oktavia Andreas (Lembaga Yasin AlSys, 2026)
The development of practical instructional media in building engineering education is essential for supporting students’ understanding of reinforced concrete structural concepts in accordance with applicable construction standards. However, studies that specifically develop learning media in the form of physical replicas of sloof and column reinforcement based on the Indonesian National Standard (SNI) 2847:2019 remain limited. This study aimed to develop and test the feasibility of instructional media in the form of sloof and column reinforcement replicas based on SNI 2847:2019 for use in the Praktek Dasar Batu dan Beton (Basic Masonry and Concrete Practice) course. The research employed a research and development (R&D) approach using the ADDIE development model. The study participants comprised four validators—two subject-matter experts and two media experts—and twenty-three students of the Building Engineering Education Study Program as media users. Data were collected using validation and practicality questionnaires and were analyzed using Aiken’s V index and percentage analysis. The results showed that the replica media achieved a high level of validity, with average Aiken’s V values of 0.86 from material experts and 0.94 from media experts, as well as a practicality level of 90%, which falls into the “highly practical” category. These findings indicate that the replica media are feasible and effective as practical instructional media to help students understand sloof and column reinforcement details in a concrete and standard-compliant manner, and they offer practical contributions to the development of experience-based learning media in building engineering education.